The Determinants of Hypertension and Commitment to Implementing a Nutrition Program: Application of Pender Health Promotion Model - Seyyed Kamal Mirkarimi; Maryam Maghsoudloo; Rahman Berdi Ozouni-Davaji; Vahideh Raeisi; Abdolrahman Charkazi; Mojtaba Raeisi (Mashhad University of Medical Sciences, 2018)
Background and objective: The high prevalence of hypertension and its serious complications on body organs have made the disease a major health problem in all communities across the world. Given the high burden of hypertension, the present study was aimed at investigating the determinants factors of hypertension and commitment to implementing a nutritional program based on the Pender Health Promotion Model. Methods:Across-sectional survey was conducted on 420 patients with hypertension supervised by the urban health centers of Gorgan city health district. Sampling technique was random multi-stage cluster sampling. Data was collected using a standard questionnaire based on the Pender Health Promotion Model (HPM). To analyze, descriptive methods and inferential statistical tests including independent t-test, one-way ANOVA, pearson correlation coefficient and linear regression model were used through SPSS version 18. The significance level was considered less than 0.05.    Results: The results showed that 386 (91.9%) had no drug changes based on doctor comment and 352 (83.8%) did not use any drugs to control blood pressure. Statistical tests reported that commitment to implementing nutrition program had a remarkable differences with perceived barriers (p=0.001), self-efficacy (p=0.001), feelings related to behavior (p=0.001), situational determinants (P=0.038), and interpersonal factors (p=0.001). Conclusion: The score of most constructs of the HPM was moderate; therefore, designing the effective interventions using HPM may be helpful in controlling hypertension. Paper Type:Research Article.